Counting Blessing Activity in Managing Psychological Well-Being for University Students - Akhnaf, Ardhito Faza; Nurmayanti, Alsya Alifia; Kusuma, Elda; Syahda, Marsha Aurellia; Febriandini, Thalida; Chasyavera, Feby Athasya; Qudsyi, Hazhira (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
University students are individuals who must always adapt amidst the rapid and uncertain changing times. Good psychological well-being is needed to achieve optimization in every activity, both academic and non-academic. This study aimed to determine the effectiveness of counting blessings in managing the univesity students’ psychological well-being. This study applied a nonrandomized control group design with a pretest and posttest, consisting of 28 participants having psychological well-being from low to moderate levels. The participants were divided into two groups, the experimental group and the control group. The levels of psychological well-being were measured by using The Scale of Psychological Well-being (SPWB) developed by Ryff (2014) adapted by Rihlati (2018). Psychological well-being scores of the pretest and posttest were processed by SPSS 25 for Windows. This study indicated a p value of 0.394 (p>0.05), meaning that there were no significant different levels of psychological well-being between the group performing counting blessings and the group not performing counting blessings. Then, this study also found that there were significantly different levels of psychological well-being of the participants before and after performing counting blessings with a p-value of 0.002 (p>0.05). The efforts made by each student to interpret every positive thing in their daily life are beneficial to help them have good psychological well-being.